DUAL SAKLAR KONVERTER DC-DC UNTUK CATU DAYA LAMPU LED PENERANGAN - Turahyo Turahyo (Lembaga Penelitian Universitas Balikpapan, 2021)
LED lamps have been extensively used as lighting lamps both in industry and in households. Led lamps as lighting generally use AC voltage as the power supply. This lamp is available from the supply using a voltage between 220-240 volts. However, under certain conditions a DC voltage with a level between 100-125 volts can be utilized to turn on the LED lighting. Solar cell is a power plant with an output voltage in the form of DC voltage. Solar cells used for household needs generally have an output voltage level of 6 volts to 48 volts. The output voltage cannot be employed to turn on the LED lighting. For that we need an equipment that is in a position to change the output voltage level of the solar cell into a higher voltage level. This equipment is generally called a boost DC-DC converter. In this paper, the input voltage used is 7,4 volts with an output voltage of 125 volts with a 5 watts LED lamp load. The input current absorbed in this design is 0,7 A and the output current is 0,0314 A.